A proposed clinical conceptual model for the physiotherapy management of Complex Regional Pain Syndrome (CRPS). (December 2018) - Pons, Tracey; Shipton, Edward A.; Williman, Jonathan; Mulder, Roger T.
Abstract: There are no validated clinical models to show a reliable pathway of guaranteeing an effective recovery for Complex Regional Pain Syndrome (CRPS) with physiotherapy management. An array of medical, psychological and physiotherapy intervention methods show weak benefit. Spearman correlations, with significance p < 0.05, from an observational, prospective, longitudinal, multi-centre study of regional standard physiotherapy CRPS management showed complete recovery to be potentially associated with baseline factors of: better mental health; better functional ability and quality of life; higher scores of extraversion personality trait; lower scores of intraversion personality trait; and interventions such as concurrent prescription of the anticonvulsant secondary analgesia group and a higher intensity of physiotherapy education intervention. These correlations were integrated with the literature evidence and the crux of previously suggested models to conceptualise a clinical model that can contribute to the broader knowledge of physiotherapy management in CRPS that should be tested with future research. Highlights: No models for CRPS management are validated. An integrated conceptual model is presented. Patient's perspectives may also be necessary for future models.